Relationship between physicochemical characteristics and gene expression in lettuce as a tool for genetic improvement - Alves da Silva, Eduardo; da Silva, Ernani Clarete; de Almeida Carlos, Lanamar; Mascarenhas Maciel, Gabriel; Gabriel Peres, Hugo (Comunicata Scientiae, 2022)
Alface ( Lactuca sativa L.) is a leafy vegetable worldwide consumed. It is found in its constitution vitamins and minerals, as well as bioactive compounds, such as phenolic compounds, flavonoids and anthocyanins. Since anthocyanins are responsible for the red color of the leaves and in the body prevents the appearance of non-communicable chronic diseases by the fight against free radicals. The lettuce for being present in the diet of the population becomes a promising plant for biofortification with the selection of plants with high levels of anthocyanins. The objective of the present work was to study the quantitative distribution of anthocyanin in leaves of lettuce plants of a segregating F2 population obtained from the initial crossing between two color contrasting parents (green and red).. The color, anthocyanin and flavonoid contents, as well as color correlation with anthocyanin content and the heritability of these characteristics. It was concluded that the anthocyanin content in leaves of lettuce is controlled by more than one gene with partial dominance of the genes that confer higher levels. Intense red coloration can be used as an alternative in lettuce breeding programs to identify superior lettuce genotypes with high anthocyanin content. Transgressive segregation as well as the higher heritability values observed in the studied traits will allow selecting in segregating generations, superior genotypes in accordance with the proposed objectives.